2007
DOI: 10.1111/j.1551-2916.2007.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering of Magnesia‐Doped Alumina with High Hardness and Fracture Toughness

Abstract: The effect of grain size of magnesia and its content as well as spark plasma sintering conditions on the density, grain size, strength, hardness, and toughness of alumina was investigated. Spark plasma sintering conditions were optimized at 11501C/ 5 min/1751C/min. Addition of 100 nm magnesia gave higher density levels (99.5%), while better strength (600 MPa), hardness (25 GPa), and fracture toughness (4.5 MPa . m 1/2 ) were obtained with 15 nm magnesia. The good strength and hardness is attributed to the subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 30 publications
1
32
0
2
Order By: Relevance
“…Despite the differences in material preparation and measurement techniques, the value of H 0 predicted from the present experimental data of as-sintered alumina matched well with the reported hardness value of alumina. [5][6][7]13,32] The characteristic length scale of h = 9 nm was also well within the prescribed depth, [33] up to which the gradient in local strain would affect the nanohardness data the most. The ratio of h/G (where G denotes the grain size) was negligibly small (i.e., 0.0009 for the as-sintered alumina but jumped to 0.02 for the shock-recovered alumina).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the differences in material preparation and measurement techniques, the value of H 0 predicted from the present experimental data of as-sintered alumina matched well with the reported hardness value of alumina. [5][6][7]13,32] The characteristic length scale of h = 9 nm was also well within the prescribed depth, [33] up to which the gradient in local strain would affect the nanohardness data the most. The ratio of h/G (where G denotes the grain size) was negligibly small (i.e., 0.0009 for the as-sintered alumina but jumped to 0.02 for the shock-recovered alumina).…”
Section: Resultsmentioning
confidence: 99%
“…The size of the second phase as well as the type and its thermal stability drastically influence the drag pinning force and the final grain size. 17,18 The results of Bernard-Granger and Guizard 17 showed that the influence of TiO 2 in suppression of grain growth in sub-micrometer alumina was not considerable while a significantly smaller grain size was obtained by addition of MgO particles. Chakravarty et al 18 reported that with increasing of MgO content above 1.25 wt.%, densification of sub-micron Al 2 O 3 was retarded.…”
Section: Introductionmentioning
confidence: 95%
“…reported. [5][6][7][8][9][10][11][12][13] Recent advances in nanotechnology have emerged along with numerous new nanomaterials possessing extraordinary properties. It is postulated that these nanomaterials could be incorporated into brittle ceramics to generate highly toughened composites that will be suitable for advanced engineering applications.…”
Section: Introductionmentioning
confidence: 99%